Optimization of Contact Time and Stirring Speed in The Adsorption of Cd(II) Using Acacia crassicarpa Bark Powder as Adsorbent - Hidayah, Nurul; Hanifah, Abu; Itnawita; Anita, Sofia; Devi, Silvera; Tamboesai, Emrizal Mahidin; Mukhlis (Universitas Islam Indonesia, 2025)
Acacia crassicarpa bark powder showed potential as an adsorbent due to its high cellulose content of approximately 50%. This research aimed to determine the optimum contact time, stirring speed, and adsorption kinetic models of Acacia crassicarpa bark powder for Cd(II) removal. Adsorbent characterization was conducted using a Surface Area and Pore Size Analyzer, FTIR, and SEM-EDX, while batch adsorption experiments were conducted to evaluate performance. The adsorbent exhibited a specific surface area of 0.460 m²/g and pore diameters ranging from 32.707 to 45.426 Å, indicating mesoporous characteristics. FTIR analysis identified functional groups such as O–H, C=O, and O–Cd. SEM-EDX analysis before adsorption revealed a rough surface with open, irregular pores and dominant elements including C, N, and O. After adsorption, the surface appeared smoother, with pores filled by Cd(II), as confirmed by Cd peaks in the EDX spectrum. Optimum conditions were obtained at a contact time of 70 minutes and a stirring speed of 120 rpm, resulting in an adsorption efficiency of 96.93% and a 1.3613 mg/g capacity. The adsorption kinetics followed a pseudo-second-order model (R2 = 0.9985), indicating that the adsorption mechanism occurred via chemisorption.